Heat Treatment Effects on Chemical Short-Range Ordering and Mechanical Properties of NiV Alloy - Chaker, Omran Radwan (2025)
A Master of Science thesis in Mechanical Engineering by Omran Radwan Chaker entitled, “Heat Treatment Effects on Chemical Short-Range Ordering and Mechanical Properties of NiV Alloy”, submitted in July 2025. Thesis advisor is Dr. Wael Abuzaid and thesis co-advisor is Dr. Mehmet Egilmez. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).